2020
DOI: 10.1016/j.ajhg.2020.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Regional Variation of Splicing QTLs in Human Brain

Abstract: A major question in human genetics is how sequence variants of broadly expressed genes produce tissue- and cell type-specific molecular phenotypes. Genetic variation of alternative splicing is a prevalent source of transcriptomic and proteomic diversity in human populations. We investigated splicing quantitative trait loci (sQTLs) in 1,209 samples from 13 human brain regions, using RNA sequencing (RNA-seq) and genotype data from the Genotype-Tissue Expression (GTEx) project. Hundreds of sQTLs were identified i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 68 publications
3
27
0
Order By: Relevance
“…Finally we wished to use MAJIQ + VOILA Modulizer to analyze differential splicing patterns between brain subregions. Previous studies focused on splicing quantitative trait loci within GTEx brain tissues found the cerebellar tissues cluster separately from other brain subregions based on splicing [15]. Our analysis of PTBP1 (Figure 3B) and pairwise analysis of the number of significant LSVs according to MAJIQ HET further supports distinct splicing patterns in cerebellar tissues (Figure S4A).…”
Section: Analysis Of Unique Cerebellar Splicing Patterns Highlights Known and Novel Regulatory Programssupporting
confidence: 75%
See 1 more Smart Citation
“…Finally we wished to use MAJIQ + VOILA Modulizer to analyze differential splicing patterns between brain subregions. Previous studies focused on splicing quantitative trait loci within GTEx brain tissues found the cerebellar tissues cluster separately from other brain subregions based on splicing [15]. Our analysis of PTBP1 (Figure 3B) and pairwise analysis of the number of significant LSVs according to MAJIQ HET further supports distinct splicing patterns in cerebellar tissues (Figure S4A).…”
Section: Analysis Of Unique Cerebellar Splicing Patterns Highlights Known and Novel Regulatory Programssupporting
confidence: 75%
“…Our approach and subsequent analysis offers several advances compared to previous efforts. For example [15] also analyzed differential splicing in brain subregion splicing but included only annotated, classical splicing events identified by rMATS. Several other GTEx analyses use LeafCutter's framework and focus on detecting sQTLs.…”
Section: Discussionmentioning
confidence: 99%
“…Several other SFs have been implicated in neurodegenerative disorders, including TIA‐1 that co‐localizes with hyperphosphorylated Tau and aggravates Tau pathology (Vanderweyde et al, 2016), but also SFPQ which is recruited into TIA‐1‐positive stress granules after oxidative stress induction, and colocalizes with Tau (Younas et al, 2020). Hundreds of splicing quantitative trait loci have been identified in distinct human brain regions, including one that disrupts a putative binding site for RBFOX2 and increases inclusion of MAPT exon 3 in cerebellar tissues (Zhang, Yang, et al, 2020). Small molecules targeting AS of Tau are currently in development and can rescue disease‐relevant AS of Tau pre‐mRNA in a variety of cellular systems, including primary neurons (Chen et al, 2020).…”
Section: Splicing and Age‐related Diseasesmentioning
confidence: 99%
“…Microexons are linked to neuronal cell types for their regulatory function 1,41 , however, in the case of Nsfl1c we find that their expression is not limited to neurons but instead exhibits regional regulation by being expressed only in HIPP. Thus, brain region can override cell-type specificity for a subset of genes, which may explain region-specific sQTLs 21 . The theoretical possibility that brain-region DIE in bulk arises purely from cell-type abundance or transcriptional activity differences is rarely observed.…”
Section: Discussionmentioning
confidence: 99%